2018
DOI: 10.1186/s12918-018-0636-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicogenomics of three insensitive munitions constituents 2,4-dinitroanisole, nitroguanidine and nitrotriazolone in the soil nematode Caenorhabditis elegans

Abstract: BackgroundEcotoxicological studies on the insensitive munitions formulation IMX-101 and its components 2,4-dinitroanisole (DNAN), nitroguanidine (NQ) and nitrotriazolone (NTO) in various organisms showed that DNAN was the main contributor to the overall toxicity of IMX-101 and suggested that the three compounds acted independently. These results motivated this toxicogenomics study to discern toxicological mechanisms for these compounds at the molecular level.MethodsHere we used the soil nematode Caenorhabditis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…S1 and Supplemental Table S1). identified in the literature (Gersich and Hopkins, 1986;Xiang et al, 2010;Scott and Crunkilton, 2000) and further confirmed using analytical chemistry in the present study were determined. We used a combination of literature values for D. pulex as well as generation of new toxicity data for previously untested chemicals to provide context for the sum toxicity of UV-degraded NQ (Table 2).…”
Section: Toxicity Screening Of Previously Identified Nq Uv-degradation Compoundssupporting
confidence: 82%
See 2 more Smart Citations
“…S1 and Supplemental Table S1). identified in the literature (Gersich and Hopkins, 1986;Xiang et al, 2010;Scott and Crunkilton, 2000) and further confirmed using analytical chemistry in the present study were determined. We used a combination of literature values for D. pulex as well as generation of new toxicity data for previously untested chemicals to provide context for the sum toxicity of UV-degraded NQ (Table 2).…”
Section: Toxicity Screening Of Previously Identified Nq Uv-degradation Compoundssupporting
confidence: 82%
“…The tubes were arranged in the outer ring of the carousel inside a Rayonet photoreactor (Model RPR-100, Southern New England Ultraviolet Co. Branford, CT) equipped with sixteen, 300 nm lightbulbs (RPR-3000A, Southern New England Ultraviolet Co.). Irradiation times were carefully controlled with a timer controller (Control Co. Webster, TX), and photon flux measured to be 1.38 ± 0.16 Â 10 À8 E per second by ferrioxalate actinometry (Goldstein and Rabani, 2008) where the formation of ferrous iron was monitored by UVevis spectroscopy (Cary 8454, Agilent, Santa Clara, CA) after chelation with FerroZine™.…”
Section: Uv-degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound DNAN also has the potential to undergo photochemical transformation (Taylor et al 2017a). It is toxic to a wide variety of aquatic species (Dodard et al 2013; Kennedy et al 2015; Stanley et al 2015; Gust et al 2018; Lotufo et al 2018) and to soil invertebrates (Dodard et al 2013; Gong et al 2018). Lotufo et al (2016) conducted bioaccumulation studies involving the uptake of DNAN by earthworms in amended soil and showed that the DNAN concentration in tissue exceeded the concentration of DNAN in soil.…”
Section: Introductionmentioning
confidence: 99%
“…It has excellent qualities as an explosive such as insensitivity and thermal and mechanical stability and is considered a potential insensitive replacement for hexahydro‐1,3,5‐triazine (RDX) in various formulations (Viswanath et al 2018). It has relatively low toxicity to tadpoles, fish, aquatic invertebrates, and soil nematodes and was found to be considerably less toxic than TNT and DNAN in comparative studies (Stanley et al 2015; Kennedy et al 2017; Pillard et al 2017; Gong et al 2018; Gust et al 2018; Lotufo et al 2018; Madeira et al 2018). The low log octanol–water partition coefficent K OW values predicted for NTO (from 0.89 to –1.19; Toghiani et al 2008) indicate a low propensity to adsorb to organic C through hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%